Protein Kinase Cε Modulates Insulin Receptor Localization and Trafficking in Mouse Embryonic Fibroblasts - Pedersen, David J. (Public Library of Science, 2013)
We have previously shown that deletion of protein kinase C epsilon (PKCε) in mice results in protection against glucose intolerance caused by a high fat diet. This was in part due to reduced insulin uptake by hepatocytes and insulin clearance, which enhanced insulin availability. Here we employed mouse embryonic fibroblasts (MEFs) derived from wildtype (WT) and PKCε-deficient (PKCε(−/−)) mice to examine this mechanistically. PKCε(−/−) MEFs exhibited reduced insulin uptake which was associated with decreased insulin receptor phosphorylation, while downstream signalling through IRS-1 and Akt was unaffected. Cellular fractionation demonstrated that PKCε deletion changed the localization of the insulin receptor, a greater proportion of which co-fractionated with flotillin-1, a marker of membrane microdomains. Insulin stimulation resulted in redistribution of the receptor in WT cells, while this was markedly reduced in PKCε(−/−) cells. These alterations in insulin receptor trafficking were associated with reduced expression of CEACAM1, a receptor substrate previously shown to modulate insulin clearance. Virally-mediated reconstitution of PKCε in MEFs increased CEACAM1 expression and partly restored the sensitivity of the receptor to insulin-stimulated redistribution. These data indicate that PKCε can affect insulin uptake in MEFs through promotion of receptor-mediated endocytosis, and that this may be mediated by regulation of CEACAM1 expression.